Assessment of Parents' Perceptions of Childhood Immunization: A Cross-Sectional Study from Pakistan - Azhar Hussain; Anam Zahid; Madeeha Malik; Mukhtar Ansari; Mojtaba Vaismoradi; Adeel Aslam; Khezar Hayat; Márió Gajdács; Shazia Jamshed (MDPI AG, 2021)
Immunization is one of the most cost-effective public health interventions, with considerable impacts on people's health. Parents' perception of their knowledge, attitude, and satisfaction is an important factor, as they may be targeted by interventions for better immunization coverage. Therefore, this study aimed to assess parents' perceptions in terms of their knowledge, attitude, and satisfaction of the immunization of their children aged less than two years of age, in two cities of Pakistan. A descriptive cross-sectional study was conducted in the vicinity of Rawalpindi and Islamabad from March to August 2019. A semi-structured questionnaire was used for the data collection on a convenient sample of parents. The questionnaire was hand-delivered to the parents by data collectors. Descriptive and inferential statistics were used for data analysis via SPSS version 22. A total of n = 382 respondents were included in the data analysis. Statistically significant differences were found between the parents' knowledge scores and their education levels and monthly incomes (p < 0.05). Parents with master's education degrees and low monthly incomes had significantly better knowledge (p < 0.05). Additionally, 96.85% of the respondents believed that child immunization was important. In addition, more than half of the respondents (57.58%) thought that the affordability of vaccines was a principal factor for delays in immunization. Although the parents' knowledge regarding the immunization of their children was not adequate, they had positive perceptions toward it.